Balanced charge transport and enhanced performance of blue quantum dot light-emitting diodes via electron transport layer doping. (25th May 2021) - Yang, Yue; Su, Liang; Feng, Nannan; Liu, Anqi; Xing, Xiaoxue; Lu, Min; Yu, William W
Abstract: The unbalanced charge transport is always a key influencing factor on the device performance of quantum dot light-emitting diodes (QLEDs), particularly for the blue QLEDs due to their large optical band gap. Here, a method of electron transport layer (ETL) doping was developed to regulate the energy levels and the carrier mobility of the ETL, which resulted in more balanced charge injection, transport and recombination in the blue emitting CdZnS/ZnS core/shell QLEDs. Consequently, an enhanced performance of blue QLEDs was achieved by modulating the charge balance through ETL doping. The maximum external quantum efficiency and luminance was dramatically increased from 2.2% to 7.3% and from 3786 cd m −2 to 9108 cd m −2, respectively. The results illustrate that charge transport layer doping is a simple and effective strategy to regulate the charge injection barrier and carrier mobility of QLEDs.